Are hybrid umbilical cord blood banks really the best of both worlds?. Issue 3 (13th May 2014) - Guilcher, Gregory M T; Fernandez, Conrad V; Joffe, Steven
Abstract : Since the first use of umbilical cord blood (UCB) as a medical therapy, the number of UCB banks worldwide has grown. Public UCB banks offer the option of altruistic donation, whereas private banks allow a product to be stored for the exclusive use of the paying client. With many more UCB products banked privately than publicly in countries such as the USA, hybrid models blending aspects of public and private banking have been proposed. One such bank is in operation in the UK. In this paper we review the hybrid UCB model and conclude that it offers limited benefit to the general public. Furthermore, compared with private banking, this model provides few advantages and potential disadvantages to private clients.